Membaca JK : biografi singkat Jusuf Kalla - Susilo, Taufik Adi. (Sleman, Jogjakarta : Garasi House Of Book, 2012)
Biography of Jusuf Kalla, former Indonesian vice president.
Includes bibliographical references (p. 163-168) and index.
Keywords: Kalla, M. Jusuf, -- 1942-; Vice-Presidents -- Indonesia -- Biography; Indonesia -- Politics and government -- 1998-